Urban Refugees’ Digital Experiences and Social Connections During Covid-19 Response in Kampala, Uganda - Sseviiri, Hakimu (2022)
The Covid-19 crisis and its aftermath challenged economies and societal sectors globally. Refugees in developing countries are particularly vulnerable to the socio-economic impacts of the Covid-19 pandemic. In Uganda, refugees significantly compose the marginalized urban population, dependent largely on the informal sector, and are severely affected by the crisis amidst limited social protection interventions. This article draws on key informant interviews with refugees and refugee-led organizations to examine the diverse ways through which social capital within refugees and host communities in Kampala enabled and shaped digitally mediated responses to sustain livelihoods, social wellbeing, and access to information and economic resources in the wake of the pandemic. The findings indicate that digitally enabled and mediated social networks and/or connections through bonds, bridges, and links are crucial in supporting refugees to cope with crisis effects. Networks of friends, families, and institutions are sustained by digital spaces that support the everyday lives of urban refugees through communication, social protection, livelihood continuity and recovery, and service improvisation during and after the crisis. The fragmented digital infrastructure, digital divide, limited government support, language barrier, and circulation of fake news challenged the utility of digital social networks in mobilizing support for refugees during the crisis. Digital technologies offer opportunities to strengthen social support and potentially mobilize refugee livelihoods in cities with fluid programs for displaced communities. The best practices around sustained multi-platform communications, technological innovations, data collection, and robust community engagement should be leveraged to garner the opportunities offered by technologies towards stimulating inclusive crisis responses.